Structural and dielectric properties of Europium based copper oxide layered perovskite material - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2017)
In this study, EuBa2Cu3O7+x (coded as Eu-123) material was synthesized by solid state reaction method and its chemical and physical properties were determined by FTIR, XRF, TGA and DTA techniques. The dielectric and impedance properties of Eu-123 were determined by HP-4194A Impedance Analyzer at room temperature. Eu-123 displays negative dielectric constant (NDC) property, which has a crucial importance for producing metamaterials. Moreover, the relaxation process of the material was also determined as pure conduction. In addition, it was revealed that application of magnetic field does not affect the NDC property of the sample but slightly changes the values of epsilon'.
Keywords: Europium based copper oxide layered materials; perovskite structure; negative dielectric constant; Nyquist plot; RELAXATION; IMPEDANCE; SPECTROSCOPY; TEMPERATURE; CONSTANT